2008
DOI: 10.1128/jcm.00973-08
|View full text |Cite
|
Sign up to set email alerts
|

Pyrazinamide Resistance among South African Multidrug-Resistant Mycobacterium tuberculosis Isolates

Abstract: Pyrazinamide is important in tuberculosis treatment, as it is bactericidal to semidormant mycobacteria not killed by other antituberculosis drugs. Pyrazinamide is also one of the cornerstone drugs retained in the treatment of multidrug-resistant tuberculosis (MDR-TB). However, due to technical difficulties, routine drug susceptibility testing of Mycobacterium tuberculosis for pyrazinamide is, in many laboratories, not performed. The objective of our study was to generate information on pyrazinamide susceptibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
65
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(81 citation statements)
references
References 15 publications
13
65
3
Order By: Relevance
“…The former was significantly higher than the latter (P Ͻ Ͻ 0.01), which implied that the MDR strains were more likely to be PZA resistant than the drug-sensitive ones. This result is similar to those in South Africa and Thailand (4,27). The importance of PZA in treating MDR-TB has been proved recently in a murine model in that all PZA-containing regimens tested showed better activities than those corresponding regimens without PZA when combined with second-line drugs (33).…”
supporting
confidence: 83%
See 1 more Smart Citation
“…The former was significantly higher than the latter (P Ͻ Ͻ 0.01), which implied that the MDR strains were more likely to be PZA resistant than the drug-sensitive ones. This result is similar to those in South Africa and Thailand (4,27). The importance of PZA in treating MDR-TB has been proved recently in a murine model in that all PZA-containing regimens tested showed better activities than those corresponding regimens without PZA when combined with second-line drugs (33).…”
supporting
confidence: 83%
“…None of the isolates with identical pncA mutations were epidemiologically linked, so the PZA-resistant strains might not have been obtained from transmission. For the mutations in pncA, 23 types of point mutations had been reported previously (8,9,21,(26)(27)(28)(29), and to our best knowledge, 10 novel types of mutations (13 strains) were first found in this study. The latter included all six types of the deletion mutations (L27, 91E, 111E, 122Q, 130-132VVG, and 131V) and four types of amino acid substitutions (D8A, S18P, F58S, and E174GϩM175R double mutation) in PZases as summarized in Table 1.…”
supporting
confidence: 52%
“…2 Since testing is not routinely performed, the prevalence of PZA resistance is not well known; however, surveillance studies have reported prevalence of 52%-78% in treatment failure or MDR-TB cases, and 2%-10% in non-MDR-TB cases. 1,7,9,10 PZA is a pro-drug that enters bacteria by passive diffusion and is converted to its active form, pyrazinoic acid (POA), by bacterial pyrazinamidase (PZAse). 6,12,19 POA is expelled from the mycobacterium by an efflux pump, it is protonated in the acidic extracellular space, and the protonated form is then reabsorbed into the bacilli, where the proton is released.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies have reported this correlation to be inconsistent, ranging between 41% and 80% [25]- [31], whereas other studies showed higher correlation ranging from 91% -97% [15] [17] [32] [33] [34]. In the current study, based on sequencing results, a correlation of 0.67 (significant at p-value < 0.05) between phenotypic resistance to PZA and pncA mutation was observed, this is comparable to majority of the previous studies, more especially to the study that was conducted in South Africa by Bishop et al, in which a correlation of 67% was also reported [35].…”
Section: Discussionmentioning
confidence: 99%